Faecal markers of intestinal inflammation in slum infants following yogurt intervention: A pilot randomized controlled trial in Bangladesh - Jannat, Kaniz; Kader, Md. Abdul; Parvez, Sarker Masud; Thomson, Russell; Rahman, Mahbubur; Kabir, Mamun; Agho, Kingsley; Haque, Rashidul; Merom, Dafna (Frontiers in Microbiomes, 2023)
Introduction We evaluated the effects of yogurt supplementation and nutrition education to low educated mothers on infant-gut health at an early age. Methods We designed a three-arm pilot randomized controlled trial with 162 infants aged 5-6 months and at risk of stunting (LAZ ≤-1 SD and >-2 SD at enrollment) living in slum areas in Dhaka, Bangladesh. Eligible children were randomized to receive, 1) nutrition education, 2) yogurt supplementation plus nutrition education or 3) usual care. Three faecal inflammatory biomarkers alpha-1 antitrypsin (AAT), myeloperoxidase (MPO), and neopterin (NEO) were measured before and after three months of yogurt feeding. Results At the end of three months, there were no significant differences in the biomarker concentrations between the yogurt plus group and control. Compared to control, the adjusted mean faecal NEO concentration decreased by 21% (NEO: RR 0.79, 95% CI: 0.60, 1.04) and the adjusted mean faecal AAT concentration decreased by 8% (AAT: RR 0.92, 95% CI: 0.69, 1.22); whereas, the adjusted mean faecal MPO concentration increased by 14% (MPO: RR 1.14, 95% CI: 0.62, 2.09). Such changes were not apparent in the education only group. Discussion After a three-month trial of daily yogurt feeding to children at risk of stunting and infant feeding education to their mothers, reduction in one inflammatory biomarker reached close to statistical significance, but not all of the measured biomarkers. The study did not finish its endline measurements at 6-month as designed due to COVID 19 pandemic. This has greatly impacted the interpretation of the results as we could not establish a decreasing trend in biomarker concentration with continued yogurt feeding.